ANALISIS KEGIATAN PENDIDIKAN KARAKTER BERBASIS PENGALAMAN DALAM MENUMBAHKAN KARAKTER SISWA DI JOGJA GREEN SCHOOL - Fadilah Rizki Nur Pratama; Retna Mega Kartika; Lena Sari Wulandari; Arum Puspa Kencana; Andriani Dini Prastiwi; Dini Mayada Wulan Juwita; Valentina Surya Ningrum; Taufik Muhtarom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to determine: 1) Implementation and concrete forms of programs at Jogja Green School in the process of character building students; 2) Implementation of the flagship nature school program oriented towards practical activities (hands-on) and life skills at Jogja Green School; 3) Obstacles and challenges faced by Jogja Green School in carrying out various character education activities. This study uses a descriptive qualitative approach method. Data were collected through participant observation techniques, in-depth interviews, and documentation. Data analysis techniques were carried out systematically following the interactive model of Miles and Huberman, which includes the stages of data reduction, data presentation, and drawing conclusions. This article analyzes the Planning, Implementation, Evaluation, and Challenges of the implementation of the flagship program Oriented Hands-On and Life Skills at Jogja Green School (JGS), an inclusive nature school established in 2009 and inspired by the Totto-chan philosophy. With 80% inclusive students, JGS emphasizes a flexible curriculum and focuses on character education including tolerance, empathy, and social values such as forgiveness to achieve 0% cases of bullying. The planning and implementation of flagship programs center on experiential learning, realized through practical (hands-on) activities such as structured planting programs, experimental science, and weekly life skills classes such as washing and ironing, which foster independence. Additionally, there is an entrepreneurship program in the form of frozen products and a market day, with proceeds donated to the orphanage, emphasizing the formation of social character and environmental awareness. Evaluation is conducted through student assessments and behavioral observations within these integrated activities. Nevertheless, JGS faces major challenges in implementing inclusion, including the need for ongoing teacher training and adapting curriculum management to meet the needs of diverse students, in line with the philosophy that every child has the right to a decent education.